The Influence of Product Innovation, Price, and Promotion on Purchase Interest Bata Shoe Consumers - Januar, Salsabila Kunti (Business and Investment Review, 2025)
This study aims to determine whether product innovation, price, and promotion influence purchase interest. The study uses a quantitative approach, with primary data collected through questionnaires. Since the exact population size is unknown, this study employs purposive sampling as the sampling method, resulting in a total of 180 respondents who are consumers of Bata shoes. Data analysis in this study is conducted using the SPSS version 26 program with multiple linear regression testing. The results of this study indicate that product innovation, price, and promotion significantly influence purchase interest. Abstrak Penelitian ini bertujuan untuk mengetahui apakah inovasi produk, harga dan promosi berpengaruh terhadap minat beli. Penelitian ini menggunakan pendekatan kuantitatif dan pengumpulan data primer menggunakan kuesioner. Karena populasi dalam penelitian tidak diketahui jumlah pastinya dan menggunakan Teknik purposive sampling sebagai metode pengambilan sampel dengan jumlah sebesar 180 responden yang merupakan konsumen Sepatu Bata. Analisis data pada penelitian ini menggunakan program SPSS versi 26 dengan pengujian regresi linear berganda. Hasil penelitian ini menunjukkan bahwa inovasi produk, harga dan minat beli berpengaruh signifikan terhadap minat beli. Kata Kunci: Inovasi Produk, Harga, Minat Beli, Sepatu Bata